Options to Improve Transparency of Environmental Monitoring Governance for Polymetallic Nodule Mining in the Area - Komaki, Kanae; Fluharty, David (Frontiers in Marine Science, 2020)
This paper proposes institutional innovations to advance a transparent monitoring system for the environmental impacts from mineral development on the deep seabed beyond national jurisdictions managed by the International Seabed Authority (ISA). Using a literature review, ISA’s regulations, and five cases of other environmental monitoring of the deep sea, this study observes that ISA's environmental monitoring system for exploration and exploitation currently lacks critical elements to facilitate transparency. Insufficient compliance reporting and review systems, as well as limited access to information by stakeholders, lower the system's effectiveness. ISA has not developed adequate mechanisms to support effective multinational collaboration in monitoring. The ISA monitoring system without these characteristics may not be sufficiently adaptive to allow detection and management of environmental changes in the deep seabed. This study suggests 15 institutional recommendations to ISA in order to enhance transparency for monitoring nodule mining in the Central Pacific deep seabed. Principal recommendations include establishing compliance review committees independent of ISA governing bodies, implementing collective monitoring and reporting by adjacent contractors, and reconsidering the centralized decision-making authority by the Secretary-General to improve confidentiality.